Encyklika Spe salvi: śladami Augustyna - Turek, Waldemar Jan (Vox Patrum, 2008)
The reading of the Encyclical Spe salvi of Benedict XVI, with a special regarding for the presence of Augustine’s sentences, gave us the opportunity to distinguish some subjects essential for the concept of Christian hope proposed by the Pope to the Christian community. Benedict XVI emphasizes in a very clear way the relation between hope and faith: „Spei substantia fides est”. The eschatological dimension of hope influences strongly the life of Christians, who continually are looking for reasons of life, of work and of ministry. In Christ our hope receives a new meaning and we are called to continue our process of purification and to open our heart to the gift which comes from God, our big Hope.